2017
DOI: 10.1002/ab.21704
|View full text |Cite
|
Sign up to set email alerts
|

The facial width‐to‐height ratio determines interpersonal distance preferences in the observer

Abstract: Facial width-to-height ratio (fWHR) is correlated with a number of aspects of aggressive behavior in men. Observers appear to be able to assess aggressiveness from male fWHR, but implications for interpersonal distance preferences have not yet been determined. This study utilized a novel computerized stop-distance task to examine interpersonal space preferences of female participants who envisioned being approached by a man; men's faces photographed posed in neutral facial expressions were shown in increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 74 publications
(128 reference statements)
1
14
0
Order By: Relevance
“…Our result is consistent with previous findings from the social psychology literature [ 61 , 62 ]. For example, Lieberz and colleagues [ 61 ] showed that women detect implicit cues of aggressiveness in male faces and adjust their interpersonal distance behaviour accordingly. Moreover, a recent study found an increased interpersonal space when an angry confederate (virtual character) approached participants [ 62 ].…”
Section: Resultssupporting
confidence: 94%
“…Our result is consistent with previous findings from the social psychology literature [ 61 , 62 ]. For example, Lieberz and colleagues [ 61 ] showed that women detect implicit cues of aggressiveness in male faces and adjust their interpersonal distance behaviour accordingly. Moreover, a recent study found an increased interpersonal space when an angry confederate (virtual character) approached participants [ 62 ].…”
Section: Resultssupporting
confidence: 94%
“…[], Geniole and McCormick [], Lieberz et al. [], Ormiston, Wong, and Haselhuhn []) . These two limitations of our study, in our view, represent potential opportunities for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, there is ample evidence suggesting that wider-faced men are indeed perceived differently. The perceptions they trigger, and the reactions they receive, may in turn shape their counter-reactions and expectations [ 4 , 43 ]. These are the kinds of recursive processes that typically arise from stereotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be more appropriate to think of fWHR-related traits in terms of social dominance and competitiveness, or perhaps “strategic” and “flexible” forms of prosociality (pursuing social status rather than ultimately prosocial goals) than in terms antisocial traits. Such understanding may help to resolve the paradox that men with high fWHR are perceived and described as successful [ 13 , 18 ] despite the evidence of their higher aggressive potential [ 1 4 ]. Nonetheless, for any such multi-faceted and context-dependent behavioral traits, it will be much harder for observers to find a reliable physical marker than it were for a consistently salient and unidimensional attribute such as “aggression” [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation